Aprendizagem lúdica em geometria molecular: uma abordagem com simuladores digitais e jogos - Araujo, Larissa de Castro Leal de (2024)
Teaching and learning chemistry is currently a challenge. Students and teachers constantly report difficulties in the classroom, and it is even possible to see that some content is easier to understand than others. Experience in the classroom makes it possible to identify how difficult it is for students to assimilate and learn the content of molecular geometry. Likewise, the growing technological evolution and the development of increasingly advanced equipment have been a major attraction for the population and, in schools, it has been no different, which makes the school environment less and less interesting. This research was carried out during the month of April 2023 and seeks to investigate and analyze the effectiveness of using the digital simulator "Monte uma Molécula", the augmented reality application "Mirage-Molecular Geometry" and the didactic game "2 ou 3D - Você em Ação" in the process of learning the content of molecular geometry in a second grade high school class, integrated into the technical course, made up of thirty-two (32) students. To this end, a qualitative and exploratory study was carried out, based on the development of a didactic sequence, organized into six stages. The research was carried out in a state school in Espírito Santo, located in the city of Cariacica. The data was collected using an identification and survey questionnaire, notes, audio recordings, photo and video analysis and, above all, observation in the field. The questionnaires were analyzed using the assumptions of the content analysis proposed by Laurence Bardin, from which it was possible to infer the students' knowledge of the concept of chemical bonds, especially molecular geometry, as well as the difficulties in assimilating the other categories analyzed. During the application of the didactic sequence, it was possible to observe the evolution of the students' knowledge-building process, as they were the protagonists of their teaching and learning process. In this way, the results show that the combination of technological resources and playfulness favors the learning of molecular geometry.